TRANSGENDER/GENDER NONBINARY STUDENTS WITH DISABILITIES: BEST PRACTICES FOR DISABILITY SUPPORT SERVICES PROVIDERS IN POSTSECONDARY EDUCATION - Cea, Dana M (East Carolina University, 2021)
There are approximately 26,600 students of public higher education in the United States of America who identify as transgender/gender nonbinary and have at least one disability. Research has focused on these two marginalized identities (i.e., gender identity, disability status) separately for college students, and there is sparse research regarding the experiences of students for whom these two identities intersect. This study addressed the gap in research by exploring which best practices used by disability support services (DSS) providers and administrators led to student academic success and elicited feedback on the best practices from these students. A survey of questions was created based upon previous research regarding the academic success of college students with disabilities and proposed best practices for supporting this group of students. Survey responses were received from recent students (n = 89) of public higher education who identified as transgender/gender nonbinary and had at least one disability. The results indicate that the majority of participants contacted disability support services at their public university or college. A relationship between contacting DSS providers and administrators and academic success was not found to be statistically significant. Additionally, the relationship between receiving accommodations from DSS providers and administrators and academic success was not found to be statistically significant. Further results demonstrated a significant association only between academic success and three practices: (1) DSS providers and administrators offering to connect students with career counseling or other vocational supports, (2) DSS providers and administrators ensuring participants' inclusion in campus activities and groups, and (3) DSS providers and administrators ensuring that school facilities are accessible for students. Finally, the best practice endorsed by the most participants was hiring staff who openly identify as having a disability. Qualitative responses from students indicated a need for responsiveness, advocacy, and accessibility from DSS providers and administrators. Limitations of this study include new instrumentation with a need for more validity and reliability information; a relatively small sample size with no demographic information gathered; and the effects of current events. Implications for DSS providers and administrators, counselor educators, and future research conclude the study.
Keywords: gender nonbinary; disability supports; postsecondary; education; best practices; Transgender Persons; Students; Gender Identity; Transsexualism; Disabled Persons